AST, ALT and Albumin Level in Chronic Hepatitis B Patients with and without Complications of Cirrhosis and Hepatocellular Carcinoma - Viky Nafi'ah Rahma Maulidia; Puspa Wardhani; Bagus Setyoboedi (Indonesian Association of Clinical Pathologist and Medical laboratory, 2020)
Complications of Chronic Hepatitis B (CHB) infection are liver cirrhosis and Hepatocellular Carcinoma (HCC). Aspartate Aminotransferase (AST), Alanine Aminotransferase (ALT), and albumin may be used as indicators of hepatocyte damage. This study aimed to determine differences between AST, ALT, and albumin in CHB patients without complications with CHB patients with cirrhosis and HCC complications. An analytical cross-sectional study was conducted in March-May 2019 on 62 CHB patients with or without cirrhosis or HCC complications using the total sampling method. AST and ALT were calculated using the Siemens Dimension device and IFCC method. The data were analyzed using independent samples T-test Albumin in CHB patients without complications was higher than CHB patients who had complications of liver cirrhosis (p=0.002). The AST and ALT were not significantly different. Aspartate aminotransferase in CHB with cirrhosis complications differed from CHB patients who had HCC complications (p=0.015), however, not different in ALT and albumin. Aspartate aminotransferase, ALT, and albumin in CHB patients without complications were different from those with HCC complications. Albumin in CHB patients without complications was different from CHB patients with cirrhosis complications. Aspartate aminotransferase in CHB patients with cirrhosis complications was different from CHB patients who had HCC complications. As a result of these differences, an integrated approach to intervening liver damage may be needed to prevent the progression of the disease from becoming more severe.